A method for selective transformation and removal of austenitic stainless steel in positive electrode active materials

By performing thermal transformation under an oxygen-containing atmosphere in the positive electrode material of lithium-ion batteries, austenitic stainless steel is transformed into a magnetic component, and removed in combination with the magnetic removal process, the problem of difficulty in removing austenitic stainless steel in the prior art is solved, and efficient magnetic differential removal and electrochemical performance are achieved.

CN115475698BActive Publication Date: 2025-03-11GEM (HUBEI) NEW ENERGY MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211112525.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-14
Publication Date
2025-03-11
Estimated Expiration
2042-09-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove the weak magnetic and non-magnetic components of austenitic stainless steel in the positive electrode materials of lithium-ion batteries, resulting in safety hazards of the battery cell.

Method used

By thermal transformation under an oxygen-containing atmosphere, austenitic stainless steel is transformed into a magnetic component and removed by means of a demagnetization process. The oxygen concentration of thermal transformation is 70-80%, and the temperature is 500-580℃.

Benefits of technology

High selective transformation and effective removal of austenitic stainless steel is achieved, transformation efficiency is improved, the problem of deterioration of active materials during thermal transformation is avoided, and the safety of the battery cell is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115475698B_ABST
    Figure CN115475698B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of cathode material modification and treatment, and specifically relates to a method for selective transformation of austenitic stainless steel in cathode active materials, wherein the cathode active materials with residual austenitic stainless steel are thermally transformed in an oxygen-containing atmosphere, and the austenitic stainless steel therein is transformed into a magnetic component; in the thermal transformation stage, the oxygen concentration in the oxygen-containing atmosphere is 70-80%, and the temperature is 500-580°C. The present invention also includes a scheme for demagnetizing the transformed raw materials to remove the magnetic anomalies after the transformation. The present invention has found that thermal transformation of the raw materials to be treated under the special oxygen concentration and temperature can unexpectedly achieve synergy, and can highly selectively transform the austenitic stainless steel therein into a magnetic component, improve the transformation efficiency, and not only that, it can also avoid the problems of "cation mixing" and residual alkali of the cathode active materials during the transformation process, and improve the performance of the removed materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of positive electrode materials, and in particular relates to a method for removing magnetic foreign matter from positive electrode active materials. Background Art

[0002] The quality of positive electrode materials for lithium-ion batteries directly affects the performance of the battery cells. Among them, the index of magnetic foreign matter (referred to as magnetic anomaly in this invention) is related to the safety of battery cell use. Magnetic foreign matter is generally measured at the ppb level, generally referring to iron and chromium, with iron being the main component. Excessive magnetic anomaly will cause the battery cell to short-circuit, thermal runaway, and then the battery cell to catch fire and explode, endangering the user's life safety. Therefore, the index of magnetic anomaly has always been the most stringent index in the lithium battery industry and a red line related to life safety. However, in the production process of positive electrode materials, the manufacturer's equipment and pipelines are all made of metal. Although it is possible to prevent magnetic anomalies from entering the positive electrode materials by spraying and adding some non-metallic materials, due to the relatively long production process, it is inevitable that magnetic anomalies caused by equipment wear and material friction will enter the positive electrode materials.

[0003] In response to the problem of excessive magnetic anomalies in active materials, the conventional solution in the industry is to perform solid-phase and liquid-phase demagnetization treatment. For example, CN113617518A discloses a method for wet removal of magnetic foreign matter from high-iron materials of lithium battery positive electrode materials. The method comprises: (1) contacting high-iron materials of lithium battery positive electrode materials with water to obtain a first slurry; (2) subjecting the first slurry to a treatment for removing magnetic foreign matter in a pipeline impurity remover to obtain a second slurry; (3) subjecting the second slurry to a solid-liquid separation treatment, and drying the obtained product to obtain a powdered material; (4) contacting the powdered material with a lithium source for sintering treatment to obtain a pure lithium battery positive electrode material.

[0004] The existing process has a certain effect on ferromagnetic components with magnetism (such as pig iron), but is basically ineffective for weakly magnetic or non-magnetic ferromagnetic components (such as austenitic stainless steel). Summary of the invention

[0005] In view of the problem that austenitic stainless steel is difficult to effectively remove through a demagnetization process if it has weak magnetism or no magnetism, the first purpose of the present invention is to provide a method for selective transformation of austenitic stainless steel in positive electrode active materials, aiming to highly selectively transform the austenitic stainless steel in the active material into a magnetic iron component, and achieve the removal method with the help of a demagnetization process.

[0006] The residual austenitic stainless steel (such as 316L, 304, 430, etc.) in the active ingredient has weak magnetism and no magnetism, and its residue will greatly affect the performance of the material. It is difficult to achieve its effective removal with the existing demagnetization process. In view of the difficulty in removing austenitic stainless steel, the inventors have previously tried to transform the austenitic stainless steel by roasting. However, the study found that, unlike the thermal transformation of austenitic stainless steel alone, when thermally transforming austenitic stainless steel in active materials, it is necessary to focus on solving the problem of deterioration of electrochemical properties caused by "cation mixing" and residual alkali of active materials during the thermal transformation process. In addition, it is also necessary to solve the problem of unsatisfactory transformation efficiency and conversion rate caused by the encapsulation and embedding of positive electrode active materials. In view of this problem, the present invention has been studied in depth and provides the following solutions:

[0007] A selective transformation method of austenitic stainless steel in a positive electrode active material, wherein the positive electrode active material with residual austenitic stainless steel is thermally transformed in an oxygen-containing atmosphere to transform the austenitic stainless steel therein into a magnetic component;

[0008] During the thermal transformation stage, the oxygen concentration in the oxygen-containing atmosphere is 70-80% and the temperature is 500-580°C.

[0009] The present invention has found that thermal transformation of the raw materials to be treated under the special oxygen concentration and temperature can unexpectedly achieve synergy and can highly selectively transform the austenitic stainless steel therein into magnetic components, thereby improving the transformation efficiency. Moreover, it can also avoid problems such as "cation mixing" and residual alkali of the positive electrode active material during the transformation process.

[0010] In the present invention, the positive electrode active material can be any positive electrode active material known in the industry, for example, it can be a lithium-ion battery positive electrode active material, and further can be an oxide of at least one element of nickel, cobalt, and manganese containing lithium, such as lithium cobaltate, lithium manganeseate, lithium nickelate, NCM ternary active material, etc.

[0011] In the present invention, the austenitic stainless steel is at least one of 316L, 304 and 430.

[0012] Preferably, in the positive electrode active material, the content of the austenitic stainless steel is not particularly required, for example, it can be above 500 ppb (calculated as iron).

[0013] In the present invention, the joint control of the oxygen concentration of the oxygen-containing atmosphere and the thermal transformation temperature is the key to synergistically achieving high-selectivity transformation of austenitic stainless steel, improving transformation effect and efficiency, and reducing the deterioration of the performance of the positive electrode active material during the transformation process.

[0014] Preferably, the oxygen-containing atmosphere is a mixed gas of oxygen and protective atmosphere, and the protective gas is, for example, nitrogen or an inert gas, and the inert gas is, for example, Ar.

[0015] Preferably, the oxygen-containing atmosphere is a gas without water and carbon dioxide. Considering the cost of processing, the oxygen-containing atmosphere in the thermal transition stage can also be a mixed gas of oxygen and air without water and carbon dioxide.

[0016] In the present invention, the thermal transformation process can be carried out with the aid of an existing gas-solid reaction device.

[0017] In the present invention, the temperature of thermal transition is preferably 500-550° C. The time of thermal transition is 10-15 hours.

[0018] The present invention also provides a selective transformation-removal method for austenitic stainless steel in positive electrode active materials. By using the method of the present invention, the austenitic stainless steel in the positive electrode active material is transformed into magnetic components and then removed under the action of magnetic force.

[0019] In the present invention, thanks to the transformation process, the weakly magnetic and non-magnetic iron components can be effectively magnetized and transformed, and can be effectively removed by combining with a simple demagnetization treatment.

[0020] In the present invention, the particle size of the product after thermal transformation is controlled to be 400-600 meshes. Then, a demagnetization treatment is performed.

[0021] In the present invention, there is no particular requirement for the strength of the magnetic force, for example, it may be 8000 Gauss or more; further, it may be 10000 to 15000 Gauss.

[0022] In the present invention, the treatment object is the positive electrode active material after demagnetization treatment. The present invention has a better application value for the transformation removal of austenitic stainless steel, but the treatment object of the present invention also allows the presence of strong magnetic impurities, which can be removed together in the transformation removal of austenitic stainless steel.

[0023] Effective Effect

[0024] The present invention can synergistically improve the transformation selectivity and efficiency of austenitic stainless steel in the positive electrode active material through the combined control of the oxygen-containing atmosphere and the special treatment temperature. Not only that, it can also effectively avoid the deterioration effect on the active material caused by the thermal transformation process.

[0025] The present invention can make the components with unqualified magnetic anomaly reworked and make the magnetic anomaly of the processed components qualified. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The JMS diagrams before and after the treatment of Example 1, wherein the left diagram is the diagram before the treatment, and the right diagram is the diagram after the treatment;

[0027] Figure 2 The figure is a circulation efficiency diagram of the raw materials of Example 1, Comparative Example 2 (620°C) and Example 1 before treatment; wherein the circulation line at the top is the circulation result of the material after treatment in Example 1; the circulation line at the bottom is the circulation result of the material after treatment in Comparative Example 2 (620°C); DETAILED DESCRIPTION

[0028] In the following cases, the magnetic anomaly removal rate refers to the removal rate of austenitic stainless steel (in terms of iron), which is calculated as follows: (iron content before treatment - iron content after treatment) / iron content before treatment * 100%.

[0029] In the present invention, the positive electrode material exceeding the standard before treatment is a material in which the austenitic stainless steel (in terms of iron) still exceeds the standard after demagnetization treatment.

[0030] Example 1

[0031] ① Place the excessive ternary cathode material NCM811 (iron content is 1500ppb) in an atmosphere furnace through a bowl;

[0032] ②Introduce oxygen-nitrogen mixed gas into the atmosphere furnace, where the oxygen concentration is required to be 70v% and the mixed gas flow rate is 1m 3 / kg(positive electrode) / h;

[0033] ③ Atmosphere furnace sintering temperature 500℃;

[0034] ④ Atmosphere furnace sintering time 12h;

[0035] ⑤Sieving screen with mesh size of 400-600 or above;

[0036] ⑥Electromagnetic iron remover, magnetic force 12000 Gauss;

[0037] Magnetic anomalies can be reduced from 1500ppb to 30ppb, and foreign matter with magnetic force can be found on the magnetic core of the iron remover.

[0038] The treated positive electrode, metal lithium, Celgard 2400 polypropylene microporous membrane separator, and electrolyte (2M LiFP4, EC:EMC:1:1) were assembled into a CR2025 button cell. The material ratio of the treated positive electrode is the treated positive electrode active material: acetylene black: PVDF = 93:4:3. After the assembled button cell was left stationary for 24 hours, a charge and discharge test was performed in CC-CV mode (temperature was 25°C), and a charge and discharge cycle test was performed at 1C. The test showed that the magnetic anomaly removal efficiency was 98% and the electrochemical performance was a cycle efficiency of 97.8%.

[0039] Example 2

[0040] Compared with Example 1, the only difference is that in step 2, the concentration of oxygen in the mixed gas is 80v%, and the other operations and parameters are the same as Example 1. The results are: the magnetic anomaly removal efficiency is 97%, and the electrochemical performance is a cycle efficiency of 97.5%.

[0041] Example 3

[0042] Compared with Example 1, the only difference is that in step 3, the sintering temperatures are: A: 580° C.; B: 550° C. Other operations and parameters are the same as in Example 1.

[0043] The result is:

[0044] A: Magnetic anomaly removal efficiency is 98.5%, and electrochemical performance is a cycle efficiency of 97%;

[0045] B: Magnetic anomaly removal efficiency is 99.0% and electrochemical performance is cycle efficiency of 99%.

[0046] Example 4

[0047] Compared with Example 1, the only difference is that the active material is NCM523 material (iron content is 1460 ppb). Other operations and parameters are the same as in Example 1.

[0048] The results are: magnetic anomaly removal efficiency is 98.5% and the electrochemical performance is a cycle efficiency of 97%.

[0049] Comparative Example 1:

[0050] Compared with Example 1, the only difference is that the oxygen content of the mixed gas in step 2 is changed to: A: 50%; B: 90%;

[0051] The results are: A: magnetic anomaly removal rate is 40%; cycle efficiency is 96%;

[0052] B: Magnetic anomaly 85%; cycle efficiency 96.5%;

[0053] Comparative Example 2:

[0054] Compared with Example 1, the only difference is that the temperature of step 3 is changed, which are: A: 450°C; B: A: 620°C;

[0055] The results are: A: magnetic anomaly removal rate is 10%; cycle efficiency is 96.5%;

[0056] B: Magnetic anomaly removal rate is 20%; cycle efficiency is 91.5%.

Claims

1. A method for selective transformation of austenitic stainless steel in a positive electrode active material, characterized in that: Thermally transforming the positive electrode active material with residual austenitic stainless steel in an oxygen-containing atmosphere to transform the austenitic stainless steel into a magnetic component; During the thermal transformation stage, the oxygen concentration in the oxygen-containing atmosphere is 70~80% and the temperature is 500~580℃.

2. The selective transformation method according to claim 1, characterized in that: The positive electrode active material is a lithium ion battery positive electrode active material.

3. The selective transformation method according to claim 2, characterized in that: The positive electrode active material is an oxide of at least one element among nickel, cobalt and manganese containing lithium.

4. The selective transformation method according to claim 3, characterized in that: The positive electrode active material is at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide and NCM ternary active materials.

5. The selective transformation method according to claim 1, characterized in that: The austenitic stainless steel is at least one of 316L, 304 and 430.

6. The selective transformation method according to claim 1, characterized in that: The oxygen-containing atmosphere is a mixed gas of oxygen and protective atmosphere.

7. The selective transformation method according to claim 1, characterized in that: The thermal transformation process takes 10 to 15 hours.

8. A method for selective transformation and removal of austenitic stainless steel in positive electrode active materials, characterized in that: The method according to any one of claims 1 to 7 is used to transform the austenitic stainless steel in the positive electrode active material into a magnetic component, which is then removed under the action of a magnetic force.

9. The selective transformation-removal method of austenitic stainless steel in the positive electrode active material according to claim 8, characterized in that: The particle size of the product after thermal transformation is controlled to be 400~600 mesh.

10. The selective transformation-removal method of austenitic stainless steel in the positive electrode active material according to claim 8, characterized in that: The strength of the magnetic force is above 8000 Gauss.

11. The method for selective transformation and removal of austenitic stainless steel in the positive electrode active material according to claim 10, characterized in that: The strength of the magnetic force is 10,000~15,000 Gauss.

12. The selective transformation-removal method of austenitic stainless steel in the positive electrode active material according to any one of claims 8 to 11, characterized in that: The positive electrode active material with residual austenitic stainless steel is the positive electrode active material after the demagnetization treatment.

Citation Information

Patent Citations

  • Method for removing magnetic foreign matters in high-iron material of lithium battery positive electrode material by wet method

    CN113617518A

  • Method for removing magnetic substance from lithium ion battery positive electrode material

    CN105244493A

  • Heat treatment process for reducing sensitization degree of austenitic stainless steel

    CN106854687A